3D printing using plant-derived cellulose and its derivatives: A review. (1st January 2019) - Dai, Lei; Cheng, Ting; Duan, Chao; Zhao, Wei; Zhang, Weipeng; Zou, Xuejun; Aspler, Joseph; Ni, Yonghao
Highlights: Up-to-date usage of cellulose and its derivatives for 3D printing. Summary of different functions of cellulose and its derivatives in 3D printing. The shear-thinning feature imparts cellulose/its derivatives with good printability. Water-soluble/water-dispersible cellulose derivatives preferred for 3D printing. Various examples of cellulose/its derivatives in 3D printing discussed. Abstract: Three-dimensional (3D) printing is classified as a revolutionary, disruptive manufacturing technology. Cellulose (the most abundant natural polymer) and its many derivatives have been widely studied for many applications. The combination of 3D printing with cellulose-based feedstocks is therefore of critical interest. This review highlights many studies on 3D printing applications of plant-derived cellulose and its derivatives. Potential materials include cellulose ethers/esters, microcrystalline cellulose, nanocellulosic materials, and other products. It focuses on their roles and functions in 3D printing processes and the performance of the resultant printed objects. The outlook for future work is also provided, to underscore critical issues and opportunities.